Acquisition resistance to bleomycin deregulates HSP77 and HSP60 proteins in response to stress - Burgos-Molina, Antonio Manuel; Alamilla Presuel, Juan Carlos; Mercado-Sáenz, Silvia; González Vidal, Alejandro; Ruiz-Gómez, Miguel José (Aseica, 2022)
The HSP77 and HSP60 protein overexpression is implicated in bleomycin resistance. The resistant adquisition to antineoplastic drugs deregulate proteins involved in response to stress factors.
Keywords: Proteínas - Análisis - Congresos; Acquisition resistance; Bleomycin; HSP77; HSP60